1998
DOI: 10.1258/1357633981931498
|View full text |Cite
|
Sign up to set email alerts
|

Telepsychiatry: an island pilot project

Abstract: A telemedicine link was established in 1996 between the island of Inishmore and the department of psychiatry in University College Hospital, Galway. The link was mainly used to facilitate emergency consultations between patients on the island and the duty psychiatrist, always at the request of the island's general practitioner. Nine patients were referred for assessment in this manner over eight months. Three patients had their first psychiatric contact and assessment through the video-link, and were followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…1,2 Recent telepsychiatry applications with adults include a range of settings such as rural areas, 3,4 inner city sites, 5,6 and prisons. 7 Case reports with adults suggest successful telemedicine intervention for Post Traumatic Stress Disorder, 8 gender identity issues, 9 depression, 10 anxiety, 11 agoraphobia, 12 and eating disorders.…”
Section: Introduction I N the Mental Health Field Psychiatristsmentioning
confidence: 99%
“…1,2 Recent telepsychiatry applications with adults include a range of settings such as rural areas, 3,4 inner city sites, 5,6 and prisons. 7 Case reports with adults suggest successful telemedicine intervention for Post Traumatic Stress Disorder, 8 gender identity issues, 9 depression, 10 anxiety, 11 agoraphobia, 12 and eating disorders.…”
Section: Introduction I N the Mental Health Field Psychiatristsmentioning
confidence: 99%
“…74 Telepsychiatry Several reports in the last decade of the twentieth century revealed that telepsychiatry was coming of age. [75][76][77][78][79][80][81][82][83][84][85][86][87] Telemedicine for patients with obsessive-compulsive disorder was reported as early as 1996. 88 In 1998 Brown reported the use of telemedicine in ''rural psychiatry''.…”
Section: Dementiamentioning
confidence: 99%
“…Mannion et al [21] established an ISDN-based telepsychiatry link between West Galway, Ireland and the Aran islands and successfully interviewed nine adult patients with good acceptance by clinicians and patients. A telepsychiatry service in Finland provided a wide range of educational, administrative and clinical services over a 2-year period [22].…”
Section: Telepsychiatry In General Populationsmentioning
confidence: 99%